2008
DOI: 10.1139/h08-073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperthermia and physical activity on circulating growth hormone

Abstract: The aim of this study was to differentiate the effects of hyperthermia and physical activity on circulating growth hormone (GH) secretion. Nine healthy volunteer adults performed two 40 min exercise trials and two 50 min passive standing trials. The exercise was performed in either thermo-neutral (N-Ex: air temperature 18 degrees C, air humidity 40%, and wet bulb globe temperature (WBGT) 17.7 degrees C) or hot environmental conditions (H-Ex: air temperature 33 degrees C, air humidity 30%, and WBGT 34.6 degrees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Additionally, GH concentrations in the FAST group were significantly greater (almost 4.5-fold) than in the SLOW group at POST, corroborating previous findings for a moderate temperature condition; specifically, the intensity of exercise (while holding total volume of work constant) directly influences the acute exercise-induced GH increase (Felsing, Brasel, & Cooper, 1992;Pritzlaff et al, 1999). Passive heating sufficient to raise core temperature by 0.8-1.2°C has been shown to elicit an acute GH response (Brandenberger et al, 1979;Møller et al, 1989); furthermore, the acute exercise-induced GH response is augmented by exercise in a hot environment (when compared to exercise in a thermoneutral environment) (Bridge, Weller, Rayson, & Jones, 2003;Ftaiti et al, 2008;Vigas, Celko, & Koska, 2000). Armstrong et al (2012) utilised ingestible gastrointestinal thermistor during the 2011 HHH event (i.e., covering the same road course and with a mean ambient temperature similar to the present study [34.4°C vs. 35.3°C]) and found an~1.6°C increase from PRE to POST ride.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, GH concentrations in the FAST group were significantly greater (almost 4.5-fold) than in the SLOW group at POST, corroborating previous findings for a moderate temperature condition; specifically, the intensity of exercise (while holding total volume of work constant) directly influences the acute exercise-induced GH increase (Felsing, Brasel, & Cooper, 1992;Pritzlaff et al, 1999). Passive heating sufficient to raise core temperature by 0.8-1.2°C has been shown to elicit an acute GH response (Brandenberger et al, 1979;Møller et al, 1989); furthermore, the acute exercise-induced GH response is augmented by exercise in a hot environment (when compared to exercise in a thermoneutral environment) (Bridge, Weller, Rayson, & Jones, 2003;Ftaiti et al, 2008;Vigas, Celko, & Koska, 2000). Armstrong et al (2012) utilised ingestible gastrointestinal thermistor during the 2011 HHH event (i.e., covering the same road course and with a mean ambient temperature similar to the present study [34.4°C vs. 35.3°C]) and found an~1.6°C increase from PRE to POST ride.…”
Section: Discussionsupporting
confidence: 86%
“…During the TT serum GH level increased by several times more than that of PRL and, differently from PRL, changes in GH level did not correlate with increases in T c . Literature shows, with a few exceptions [59,62], that GH secretion is sensitive to increases in T c [30,55,63], and that positive relationships occur between T c and GH levels during prolonged exercise in the cold [64] and in the heat [31,49,65]. However, all previous studies which revealed direct relationship between exercise-induced changes in T c and blood GH levels employed constant-load exercise of fixed duration [49,64,65] or to volitional exhaustion [31], whereas in the current study, the participants performed self-paced TT.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancies between these studies in the post-HAST changes may be related to differences in both the HA regimes (passive vs active) and HAST, with the exercise-heat stress approach employed by Timpmann et al [ 206 ] and Tamm et al [ 201 ] likely eliciting a significantly greater thermo-physiological strain than the passive sauna approach of Leppäluoto et al [ 112 ] and Pilch et al [ 166 ]. Circulating growth hormone levels are known to increase with hyperthermia [ 57 ] and thus a decrease in growth hormone concentration might be hypothesised following a period of HA concomitant with the reduction in deep body temperature. However, data on the effect of HA on growth hormone levels are similarly equivocal, with studies showing no effect following a HAST [ 146 , 147 ], an attenuated response [ 157 ] or inconsistent findings [ 55 ], although these differences are not easily attributable to protocol differences given that all employed active HA and HAST approaches, they might be influenced by the pulsatile nature of growth hormone release [ 75 ].…”
Section: Candidate Biomarkersmentioning
confidence: 99%